O mundo existencial do aluno na aula de Ciências: perspectiva fenomenológica no ensino de Ciências na escola publica de 1º grau ( 5a. à 8º. séries) - Shimamoto, Delma Faria (1993)
Qiualitative study of the meaningful connection/disconnection between the student´s existencial world and the formal process in teaching-learning Scienes at public e elementary school,, I±. proceda to the description and phenomenolooical existencial inter. pretation of the discourse of teachers, student'5 and educacional advisers in the case of 05 (five) 5 rate schools belonging to the 2óth„ Regional Schoool District in Uberlândia . UG „ Becomes evident a disconnection of meaning between formal process of teaching ..learning Science and the student´s existencial world.